An experimental methodology to assess the climate impact on the energy performance of buildings: A ten-year evaluation in temperate and cold desert areas. (15th April 2020) - Sánchez, M.N.; Soutullo, S.; Olmedo, R.; Bravo, D.; Castaño, S.; Jiménez, M.J.
Highlights: Experimental methodology to assess the climate impact on the performance of buildings. Ten-year monitoring campaign in temperate climate and cold desert climate. Climate trends evaluation in an average and a typical hot climate scenarios. Climate bias, average and extreme patterns, building energy demand and comfort. Annual trends show warmer and drier climates in assessed locations: Csa and BWk. Abstract: An experimental methodology has been developed to evaluate the climate impact assessment on the energy performance of buildings based on real weather data. This new methodology has been applied in Madrid and Tabernas, respectively characterized by temperate and cold desert climates. A systematic study has been conducted supported by a ten-year test campaign from 2008 to 2017, analysing an average year and a typical hot year. Annual and seasonal experimental values have been compared with typical meteorological years, synthetically created for Madrid (1981–2010) and Tabernas (1972–2000). Madrid registered an increase in air temperature of 0.6 °C in the average year and of 0.9 °C in the typical hot year, compared to the synthetic year. In Tabernas, the increase in air temperature was 2.4 °C and 2.7 °C respectively. Climate indices and surface maps of temperature, relative humidity and solar global radiation have confirmed the same climatic trends. To evaluate how climate change affects the building energy performance, heating and cooling degree days have been calculated. The typical hot year has the highest value of 200°days for the cooling index in summer and the average year has the highest value of about 1000°days for the heating index in winter, both registered in the temperate climate. Finally, a bioclimatic analysis concluded that in temperate climates, cooling strategies have to be enhanced in summer and early fall. On the contrary, in the desert climates it is worth noting the increase in comfort hours in spring and autumn.